2009
DOI: 10.1111/j.1365-2141.2008.07551.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and molecular features of persistent polyclonal B‐cell lymphocytosis (PPBL) with progressive splenomegaly

Abstract: Five cases of persistent polyclonal B-cell lymphocytosis (PPBL) with progressive splenomegaly are reported; three were splenectomized. BCL2/IGH rearrangements were found in three cases; HLA-DRB1*07 in all. Bone marrow (BM) trephines showed a moderate lymphoid infiltrate with intrasinusoidal distribution resembling a splenic marginal-zone lymphoma. Splenic white pulp revealed an enlargement of the marginal-zone area; red pulp was infiltrated by the same lymphocytes engulfing the sinuses. Splenic and BM B-lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…In their series of 5 patients Del Giudice et al from Italy recently reported very similar findings to ours in three of their five PPBL patients who developed massive splenomegaly and underwent splenectomy [8]. The B cells present both in bone marrow and spleen show same immunophenotype including expression of BCL-2 [7,8]. In addition, the B cells in our patient were also positive for CD43.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In their series of 5 patients Del Giudice et al from Italy recently reported very similar findings to ours in three of their five PPBL patients who developed massive splenomegaly and underwent splenectomy [8]. The B cells present both in bone marrow and spleen show same immunophenotype including expression of BCL-2 [7,8]. In addition, the B cells in our patient were also positive for CD43.…”
Section: Discussionsupporting
confidence: 85%
“…We here report histological and immunohistochemical features of the spleen in a young female with PPBL who underwent splenectomy due to progressive splenomegaly on her 6 th annual follow-up. Very recently, Italian investigators Del Giudice et al described similar histopathological findings of the spleen in three patients with PPBL and progressive splenomegaly who underwent splenectomy [8]. PPBL can be further confused with a malignant lymphoproliferative disorder as PPBL is frequently associated with chromosomal abnormalities and multiple BCL2/IG gene rearrangements as seen in some lymphomas [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some features could suggest a link between PPBL and SMZL. Both entities share same histologic patterns: 1/expansion of the white pulp of the spleen, with an enlargement of the marginal zone area of the follicles, and an intrasinusoidal infiltration of the red pulp [7,8] and 2/ intrasinusoidal infiltration by polyclonal B-cells in bone marrow [7,9]. Phenotypical characterization by MFC is also similar between the two entities, with the expression of surface IgM, CD19, CD20 and CD79b, but lacking the expression of CD5, CD10, CD23, CD43 and CD103 (WHO classification, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Patterns are generally mixed in any individual specimen, apart from pure paratrabecular involvement in some cases of FL and pure nodular infiltration in some examples of SLL/CLL. Pure or almost exclusively intrasinusoidal small B-cell infiltration should raise the possibility of persistent polyclonal B lymphocytosis, a rare disorder found typically in female patients who are heavy smokers 17. The cellular immunophenotype in persistent polyclonal B lymphocytosis resembles that of SMZL apart from the absence of light chain restriction.…”
Section: Lymphoid Infiltratesmentioning
confidence: 99%